2005
DOI: 10.1007/s11095-005-5281-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Microcrystallinity of a Drug Substance, Indomethacin, in a Pharmaceutical Model Tablet by Chemometric FT-Raman Spectroscopy

Abstract: The established technique is ideally suited for precise quantification of microanalysis of drug substances and drug products, particularly at the surface and interior of the tablet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…Wet granulation and subsequent drying Raman spectroscopy Paracetamol [140] Amorphisation and recrystallisation Melting and cooling API-polymer mixtures Micro FTIR spectroscopy Indometacin [141] Solid-solid amorphisation of crystalline indometacin to amorphous indometacin Solid-state conversion induced by pressure…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wet granulation and subsequent drying Raman spectroscopy Paracetamol [140] Amorphisation and recrystallisation Melting and cooling API-polymer mixtures Micro FTIR spectroscopy Indometacin [141] Solid-solid amorphisation of crystalline indometacin to amorphous indometacin Solid-state conversion induced by pressure…”
Section: Discussionmentioning
confidence: 99%
“…A pressure-induced amorphisation of indometacin was observed in a study that aimed to establish a PLS method to determine the microcrystallinity of indometacin in model compacts of indometacin and mannitol based on Raman spectroscopy. [141] Crystalline indometacin was found to undergo a conversion to amorphous indometacin, which was more pronounced at higher compaction pressures. Furthermore, differences in microcrystallinity of indometacin at the surface and the interior of the compact could be described and showed the value of the Raman spectroscopic PLS model.…”
Section: Amorphous Formsmentioning
confidence: 95%
“…Owing to its ease and rapidity, IR spectroscopy was used to determine polymorph contamination during process development (Vogt et al, 2005). Some authors have reported the use of these techniques for the analysis of materials with different degrees of crystallinity (Okumura and Otsuka, 2005) and solid dispersions (Konno and Taylor, 2006). Raman spectroscopy was used to detect amorphous indomethacin at a level of 2% w/w using a calibration curve of indomethacin with various degrees of crystallinity.…”
Section: Vibrational Spectroscopymentioning
confidence: 99%
“…Raman spectroscopy is known as an excellent technique for the characterization of pharmaceutical products, especially for the study of solid-state medicaments, because it does not need manipulation or destruction of samples, can determine more than one component at the same time, and avoids the interference of water in the analyses. Raman technique has thus been widely applied to the pharmaceutical industry and the characterization of tablets, such as ecstasy [4], indomethacin [5] and ambroxol [6]. Applications of Raman spectroscopy in tablet analysis has extensively reported, such as solid-state evaluation, polymorphic forms analysis, investigation of coating characteristics, quantitative determination [7,8], and particularly in the identification of pharmaceutical drugs [9] and counterfeits [10][11][12].…”
Section: Introductionmentioning
confidence: 99%